HUBUNGAN KONDISI KERJA DENGAN STRES KERJA PERAWAT DIRUNGAN INTASALASI GAWAT DARURAT MEDIK RSUP PROF. DR. R. D. KANDOU MANADO - Lumingkewas, Mega; Warouw, Herman; Hamel, Rivelino (JURNAL KEPERAWATAN, 2015)
Abstract: Condition of job cover environmental variable of physical like office hours distribution, existing condition of physical goodness in the form of noise, demand and regulation, and also social relation, temperature, workplace architecture marking and lighting of voice. Target of this Research is Relations between Job’s Conditions and Nurse’s Working Stress Room Installation Serious Condition Emergency Sis of RSUP. Prof. Dr R. D. Kandou Manado. This Design Research is Analytic Survey with approach of Cross sectional. All nurses on Emergency Medic Room RSUP. Prof. DR R. D. Kandou Manado. With the number of nurses are 31 people with Intake of sample in this research use Total technique of Sampling, instrument used is used by data analysis and questioner is bivariate and univariate with test of Chi-Square. The Result of this research there are very real relations between Job’s Conditions and Nurse’s Working Stress (p=0.001). Pursuant to result of research, hence Conclusion that Job’s Conditions reside in balmy category counted 22 (71%) responder, and Working Stress mostly the included in Light category that is 25 (80.6 %) responder, hence from that better the condition of job adapted for leeway and schedule which enough in order not to happened stress in work. Keyword: Job’s Condition, Nurse’s Working Stress Abstrak: Kondisi kerja meliputi variabel lingkungan fisik seperti distribusi jam kerja, kondisi yang ada baik fisik berupa kebisingan, peraturan dan tuntutan, serta hubungan sosial, suhu, penerangan,suara dan ciri-ciri arsitektur tempat kerja. Tujuan Penelitian ini ialah Hubungan Kondisi Kerja Dengan Stres Kerja Perawat Di Ruangan Instalasi Gawat Darurat Medik RSUP. Prof. Dr. R. D. Kandou Manado. Desain penelitian ini adalah Survei Analitik dengan pendekatan Cross sectional. Seluruh perawat IGDM RSUP. Prof. DR. R. D. Kandou Manado. Dengan jumlah perawat ada 31 orang dengan Pengambilan sampel dalam penelitian ini menggunakan teknik Total Sampling, instrument yang digunakan ialah kuesioner dan analisa data yang digunakan univariat dan bivariat dengan uji Chi-square. Hasil penelitian terdapat hubungan yang sangat nyata antara Kondisi Kerja Dengan Stres Kerja Perawat (p=0.001). Berdasarkan hasil penelitian, maka Kesimpulan bahwa Kondisi Kerja berada pada kategori nyaman sebanyak 22 (71%) responden, dan Stres Kerja yang sebagian besar termasuk dalam kategori Ringan yaitu 25 (80.6 %) responden, maka dari itu sebaiknya kondisi kerja disesuaikan dengan jadwal dan waktu luang yang cukup agar tidak terjadi stres dalam pekerjaan. Kata Kunci : kondis kerja dan stress kerja perawat